2014
DOI: 10.1111/aos.12346
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors associated with age‐related macular degeneration: the Tromsø Study

Abstract: ABSTRACT.Purpose: To examine associations between cardiovascular risk factors and agerelated macular degeneration (AMD). Methods: A population-based, cross-sectional study of Caucasians aged 65-87 years was conducted in Norway in 2007/2008. Retinal photographs were graded for AMD. Multivariable logistic regression analyses were performed based on questionnaires addressing habits of smoking, alcohol consumption, physical activity, health and medication; and physical examination comprising anthropometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 41 publications
(45 reference statements)
1
43
0
2
Order By: Relevance
“…In the Tromsø study, a population-based, cross-sectional study of Caucasians aged 65-87 years conducted in Norway in 2007/2008, late AMD was found to be related to higher systolic blood pressure in women only, as were other factors associated with hypertension, such as physical inactivity, overweight and obesity [43]. In prospective studies, increased blood pressure has been found to be associated with incident AMD [44].…”
Section: Essential Hypertension As a Risk Factor For Age-related Macumentioning
confidence: 99%
See 2 more Smart Citations
“…In the Tromsø study, a population-based, cross-sectional study of Caucasians aged 65-87 years conducted in Norway in 2007/2008, late AMD was found to be related to higher systolic blood pressure in women only, as were other factors associated with hypertension, such as physical inactivity, overweight and obesity [43]. In prospective studies, increased blood pressure has been found to be associated with incident AMD [44].…”
Section: Essential Hypertension As a Risk Factor For Age-related Macumentioning
confidence: 99%
“…Furthermore, from a substudy that investigated the association between a history of vasodilator and blood pressure-lowering drug use and the incidence and progression of early and late AMD, it emerged that oral nitroglycerin (HR, 1.81; 95% CI, 1.14-2.90) was associated with an increased risk of early AMD, whereas oral b-blocking agents treatment was associated with an increased risk of incident exudative AMD [hazard ratio (HR), 1.71; 95% CI, 1.04-2.82], but not pure geographic atrophy (HR, 0.51; 95% CI, 0.20-1.29) or AMD progression (HR, 0.92; 95% CI, 0.67-1.28) over a 20-year period Table 2 [33,34,37,38,40,41,[43][44][45][46][47][48][49][50]58]. The mechanisms leading to the above observations are not easy to understand, especially when we consider that vasoconstriction of the retinal and choroidal vessels seems to be involved in the pathogenesis of AMD, while vasodilators have been used to resolve the vasoconstriction.…”
Section: Treatment Of Hypertension and Age-related Macular Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Though its complete aetiology and pathogenesis are yet to be clarified, it might be possible to alter the prevalence and incidence of ARMD by acting on modifiable risk factors [29], despite a given genetic background [30], by modifying specific habits such as smoking and dietary intake of antioxidants [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, female sex, smoking, and obesity (body mass index [BMI] > 30) are most commonly reported as important demographic and environmental risk factors for the development of AMD. [1][2][3][4][5][6] In addition, several important genetic variants have been found to be associated with AMD, either as a risk factor or as a protective factor. The strongest associations have been reported for the singlenucleotide polymorphisms (SNPs) in the complement factor H gene (CFH Y402H; rs1061170), and in the age-related maculopathy susceptibility 2 gene (ARMS2 A69S; rs10490924), which strongly increase the risk of developing AMD.…”
mentioning
confidence: 99%